2015
DOI: 10.3233/jvr-150760
|View full text |Cite
|
Sign up to set email alerts
|

Vocational rehabilitation services and outcomes for transition-age youth with visual impairments and blindness

Abstract: OBJECTIVE:This study examined data provided by the U.S. Department of Education's Rehabilitation Services Administration (RSA) in an effort to evaluate the impact of demographic variables, vocational rehabilitation services, and agency characteristics on the employment outcomes obtained by transition-age youth (i.e., 16 to 25 years old) with visual impairments and blindness. RESULTS: Results indicated that young adults who were male, Hispanic, between the ages of 23 and 25, not receiving Social Security disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 10 publications
3
45
2
Order By: Relevance
“…These studies can provide insight into factors that may be associated with employment for VR consumers who are deaf-blind. In some cases, researchers focused on specific subgroups such as consumers with congenital hearing loss (Moore, 2002), transition-age youth with visual impairments (Cimera, Rumrill, Chan, Kaya, & Bezyak, 2015; Giesen & Cavenaugh, 2012), consumers who received college or university training (Boutin & Wilson, 2009), and Social Security Disability Insurance (SSDI) beneficiaries (Giesen & Cavenaugh, 2013; Giesen & Hierholzer, 2016).…”
Section: Vocational Rehabilitation (Vr) Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies can provide insight into factors that may be associated with employment for VR consumers who are deaf-blind. In some cases, researchers focused on specific subgroups such as consumers with congenital hearing loss (Moore, 2002), transition-age youth with visual impairments (Cimera, Rumrill, Chan, Kaya, & Bezyak, 2015; Giesen & Cavenaugh, 2012), consumers who received college or university training (Boutin & Wilson, 2009), and Social Security Disability Insurance (SSDI) beneficiaries (Giesen & Cavenaugh, 2013; Giesen & Hierholzer, 2016).…”
Section: Vocational Rehabilitation (Vr) Researchmentioning
confidence: 99%
“…outcomes for transition-age youth who are blind or visually impaired (Cimera et al, 2015;Giesen & Cavenaugh, 2012), but not for adults with visual impairments (Giesen & Cavenaugh, 2013;McDonnall, 2016) or consumers who are deaf or hard of hearing (Bradley et al, 2013). In some studies, younger age was associated with positive employment outcomes (Capella-McDonnall, 2001;Darensbourg, 2013;Estrada-Hernández, 2008;McDonnall, 2016), and older age was associated with positive outcomes in another (Dutta et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, AT was clearly an important strategy for engagement in productivity as discussed by participants in this study and supported by other recent research reports. For example, Cimera and colleagues [28] found that young adults who were blind and visually impaired who received AT through a vocational rehabilitation program were more likely to find employment, and Denny-Brown et al [29] highlighted how workers with disabilities relied on AT to prepare for and get to work, as well as to accomplish job-related tasks. However, these latter two examples must be tempered by the current findings and those of others [30] that clearly illustrate the individualized nature of AT.…”
Section: Discussionmentioning
confidence: 99%